Pengaruh Perceived Risk, Perceived Benefit dan Moderasi Word Of Mouth Pada Investasi Emas Digital - Ifti Faiyah, Laila; Pertiwi Mareta, Adhe; Ridwansyah; Ruslan Abdul Ghani, Wan; Ryas Fatiha Kesuma, Muhammad; Azizah Hasanah, Nur; Aisyah Nuraini, Siti; Setiawan, Hengki (Indonesian Journal of Islamic Economics and Business, 2025)
Digital gold investment is now increasingly in demand as one of the popular investment options. The development of technology has accelerated the flow of information to have an impact on understanding people's behavior in managing finances. Advances in financial technology (fintech) have encouraged the emergence of financial management, which not only functions as a means to meet needs, but also as a strategy to build and accumulate wealth by investing. This study uses quantitative research methods namely SEM (Strructural Equation Modelling) and inductive approach analysis of data collection with survey methods. The results of this study show that perceived risk has a positive and significant effect on behavior intention, which means that the higher the perceived risk, the greater a person's intention to behave in the context under study. Perceived benefit does not have a significant effect on behavior intention, so perceived benefits are not the main factor driving a person's intention to invest. WoM does not significantly weaken the relationship between perceived risk and behavior intention, which suggests that communication from others is not strong enough to reduce the impact of perceived risk on behavior intention. WoM also does not significantly strengthen the relationship between perceived benefit and behavior intention, which means that the influence of perceived benefits on behavior intention is not strengthened by recommendations or information from others.